Evaluation of Dribbling Skills in Futsal among Elementary School Students at Muhammadiyah Imam Syuhodo - Afan Harsono; Syabrina Nurlaksa Al Fitri; Syiqul Izzah Al-Khukmi; Gatot Jariono (Universitas Negeri Semarang, 2026)
This study aimed to analyze the level of dribbling skills among elementary school students participating in extracurricular futsal activities at Muhammadiyah Imam Syuhodo Elementary School. The research subjects consisted of 40 students who were actively involved in the school’s futsal extracurricular program. A quantitative descriptive approach was employed using a survey method, with data collected through standardized dribbling skill tests and direct movement observations. The assessment focused on three main movement components: the initial stance, ball contact movement, and the final stance. The results of the study showed that the overall dribbling skill level of students was categorized as moderate, with variations across the assessed components. The initial stance component demonstrated relatively better performance, as most students were able to adopt a basic ready position before dribbling. However, weaknesses were identified in the ball contact movement, particularly in controlling the ball while moving at speed. The lowest performance was found in the final stance component, where many students had difficulty maintaining balance and proper body posture after completing the dribble. The implications of this study emphasize the need for more structured, systematic, and repetitive training programs to enhance fundamental futsal skills among elementary school students. It is recommended that coaches and physical education teachers prioritize basic dribbling techniques through varied and enjoyable training methods, while also improving supporting sports facilities at the school. This study is expected to serve as a reference for developing more effective futsal training programs in elementary school physical education contexts.